Forage availability in caribou range - Leblond, Mathieu; Dussault, Christian; Ouellet, Jean-Pierre; St-Laurent, Martin-Hugues (Dryad Digital Repository, 2016)
Habitat characteristics measured in the field to quantify forage availability in the range of the Charlevoix caribou population, Québec, Canada, 2007-2008.